Risk Factors for Development and Severity of COVID-19 in COPD Patients - Bonato, Matteo; Semenzato, Umberto; Tinè, Mariaenrica; Bazzan, Erica; Damin, Marco; Biondini, Davide; Casara, Alvise; Romagnoli, Micaela; Turato, Graziella; Cosio, Manuel G.; Saetta, Marina; Baraldo, Simonetta (Frontiers in Medicine, 2021)
The impact that COVID-19 could have on patients with COPD is a real concern. In this study we evaluated, in a cohort of longitudinally followed COPD subjects, the incidence of COVID-19, seeking for possible risk factors and prognostic factors predicting the clinical outcome. In our cohort of 370 patients (followed for 5.3±2.7 yrs), 22 developed COVID-19 (COPD/COVID-19+) between February/November 2020 (5.9%). Cardio-metabolic conditions (hypertension, dyslipidemia, obesity, diabetes) but not respiratory abnormalities (FEV1, DLCO, emphysema and exacerbations history), were risk factors for development of COVID-19 in COPD patients. Out of the 22 COPD/COVID-19+ patients, 10 needed intensive care. Low DLCO and emphysema but also metabolic comorbidities, were related to the need for intensive care.